HEGEMONY IN HAMKA’S NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK - M. Manugeren; Puja Priandana; Jumino Suhadi (Universitas Islam Sumatera Utara, 2023)
The research discusses the issue of hegemony in Hamka’s novel Tenggelamnya Kapal Van Der Wijck. The work is apparently coded with custom system in its society and can be seen as a reflection of social reality. The novel explores the custom system in Minangkabau society and reveals that nearly every member of the society is bound by the existing cultural norms. From one side, the cultural system gives a good guideline for the people; but on the other side, the hegemony within the cultural systems brings the people into rigidity. No one is brave enough to stand against the hegemony of the existing norms. The research focuses solely on the form of hegemony practices done by the elders in Minangkabau culture. This research is done by descriptive qualitative method through literary sociological approach by using the theory of power of hegemony proposed by Antonio Gramsci. The data are obtained by using reading and noting technique. The data source is the novel Tenggelamnya Kapal Van Der Wijck by Hamka. The results of the research consist of two points; (1) hegemony in the form of ideology namely authoritarianism. (2) hegemony in the forms of culture namely kinship system and social stratification in Minangkabau.